TAK PERLU MENCARI SENSASI LEWAT MEDIA SOSIAL, UNJUK BAKAT JUGA DAPAT MEMBUATMU TERKENAL - Tranggono Tranggono; Moh. Akbar Habibi; Eka Putri Oktaviana; Latifah Az-Zahidah; Naremdra Manggala Suryo Laksono; Bayu Aji Satriya (Gapenas Publisher, 2023)
Social media is one of the impacts of increasingly sophisticated technological developments, which can make everyday life easier. But it can also give a bad influence if not used wisely. Especially in this day and age, social media has become a daily staple. From day to day the influence of social media is increasingly being felt, there is no doubt about the many benefits of social media. However, now there is also a lot of misuse of social media. Where now there are many things or some kind of content that is less useful. there is no doubt that there are many benefits that can be drawn from this content, but there is also content that contains unclear and useful things. The purpose of this research is to find out what are the reasons for creating unclear and useful content on social media. As well as to provide advice to social media users so they can use social media more wisely. This research method through descriptive qualitative method. The results of the research found that the purpose of people creating content that is not clear or other strange things is to be famous so they can become celebrities. because on social media it is very easy to spread information very quickly. the conclusion is that nowadays there are lots of people who want to be famous quickly on social media, they do anything to make themselves known by many people even in a bad way. seeking fame can be like showing our talents and achievements as children of the nation we live in. share it with the public because on social media if we do bad things then it will be difficult to get rid of while if we do good things there will be lots of good things to come